2016
DOI: 10.2109/jcersj2.15317
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mordenite and its composite material using chemical reagents for Cs decontamination

Abstract: Mordenite was synthesized using chemical reagents of amorphous SiO 2 and sodium aluminate without the addition of a template agent and a seed powder. The single phase of the mordenite was obtained for the Al/Si ratios of 0.0850.120 as the starting material in the reaction temperature range of 170200°C for 24 h. The cation exchange capacity (CEC) was ca. 180210 cmol/kg and it increased with the Al/Si ratio. The Cs + adsorption ability from 100 ppm Cs + 100 mL solutions of water and seawater for the mordenite (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Zeolites, a group of aluminosilicate compounds that are widely used as adsorbents in environmental remediation, have been combined with magnetic particles, to improve the performance of adsorbents. The preparation of magnetic zeolites using conventional hydrothermal methods with different frameworks has been reported, including P zeolite [ 110 ], ZSM-5 [ 115 ], NaA [ 118 ], and mordenite [ 111 ]. The synthesis begins by mixing Fe 3 O 4 with a zeolite precursor solution, before transferring it to a stainless steel autoclave, followed by crystallization at specific temperatures, for a determined amount of time.…”
Section: Conventional Synthesis Methods Of Magnetic Adsorbentsmentioning
confidence: 99%
“…Zeolites, a group of aluminosilicate compounds that are widely used as adsorbents in environmental remediation, have been combined with magnetic particles, to improve the performance of adsorbents. The preparation of magnetic zeolites using conventional hydrothermal methods with different frameworks has been reported, including P zeolite [ 110 ], ZSM-5 [ 115 ], NaA [ 118 ], and mordenite [ 111 ]. The synthesis begins by mixing Fe 3 O 4 with a zeolite precursor solution, before transferring it to a stainless steel autoclave, followed by crystallization at specific temperatures, for a determined amount of time.…”
Section: Conventional Synthesis Methods Of Magnetic Adsorbentsmentioning
confidence: 99%
“…This mixture was heated at 170°C for 24 h in an autoclave, and then washed several times by centrifugal separation with deionized water to remove the excess alkali. It was next dried at 70°C for 24 h. Another mordenite was also prepared using chemical reagents for as the control comparison (Sample (b)) [21].…”
Section: Preparation Of Mordenitementioning
confidence: 99%
“…For the rice husk ash, the main phase was the amorphous silica with potassium oxide as an impurity. The calcination temperature of 700°C was selected for the preparation of the rice husk ash, because amorphous SiO 2 powder was necessary for the reaction using the NaOH solution [21]. In this case, the yield of the rice husk ash was 15.7 wt% from the rice husk.…”
Section: Preparation Of the Mordenitementioning
confidence: 99%
See 1 more Smart Citation
“…Degradation mechanism of parathion methyl by mesoporous MnO 2 .A. Hiromichi et al[101] (2016) reported synthesis of mordenite zeolite and its composite material using for toxic Cs ion decontamination. Reagents SiO 2 and NaAlO 2 used for synthesis without addition of a template and a seed powder.…”
mentioning
confidence: 99%